Content-related quality of food supplements with vitamin D on the market of Republic of Srpska - Ljubica Bojanić; Mirjana Djermanovic (Биомедицинска истраживања, 2023)
Introduction: Vitamin D is a liposoluble vitamin that has many important roles in the human body. Daily requirements for vitamin D are met through intake of food and exposure to sunlight. The high frequency of vitamin D deficiency is a public health problem that can be corrected using food supplements (FS), which is why its consumption is increasing. The quality of FS, including the content of active components, depends on the good manufacturing practice which is not strictly regulated for the production of FS, as well as the formulation, packaging and storage. Because of that, the quality of FS can be variable. The aim of our pilot study was to examine the conformity of the actual determined content of vitamin D and the declared content in 49 FS, in the form of tablets and capsules, present on the market in Republic of Srpska. Method: Determination of vitamin D content was performed by high-performance liquid chromatography (HPLC). Results: The range of the determined content of vitamin D in relation to the declared content, expressed as a percentage, was from 64,4% to 188,8%, whereby the deviation is not statistically significant (mean: 100.50%; Cl 95% -0.54 to 0.17; p=0.313 tablets; mean: 98.02%; Cl 95% -3.00 to 0.42; p=0.127 capsules). When measurement uncertainty is taken into account, only one sample (2.0%) was outside the legally allowed range (88.8% more than labeled). Conclusion: Therefore, it has been shown that most of the examined products are of satisfactory quality in terms of vitamin D content, but it is necessary to continuously monitor the food supplements that are on the market.
Keywords: cholecalciferol; food supplements; safety; label; HPLC